ANALISIS KOMITMEN MANAJEMEN TERHADAP PEMENUHAN HAK KEAMANAN DAN KESELAMATAN PENGUNUNG DI WISATA TUBING GOA PINDUL - Dwita Citra Andini; Bina Kurniawan; Ida Wahyuni (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2019)
Goa Pindul is one of the destinations that offer cave tubing, that is activities along the cave using a float tire by utilizing the river flow. This activity is inseparable from threatening dangers, such as holes (slope of steep riverbed), entrapment (the tire gets stuck), undercut (holes under rocks in the river), drowned, and the danger of flooding that comes at any time. The purpose of this research is to analyze management’s commitment to fulfilling the security and safety rights of visitors in Pindul cave tubing. This research is a descriptive study with a qualitative approach. The main informants were 4 people and triangulantions were 3 people. The instruments in this study used indepth interview guidelines and observation sheets. Based on the results of research on management’s commitment to fulfilling the security and safety rights of visitors in Pindul cave tubing, this is generally in accordance with the basic reference of the Tourism Law, Government Regulation concerning Application of Occupational Safety and Health Management System, Regulation of the Minister of Labor and Transmigration of the Republic Indonesia concerning First Aid on Accidents in Workplace, and management theory.